2018
DOI: 10.1016/j.gaitpost.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor control and neuromuscular activity of the shoulder in adolescent competitive swimmers with generalized joint hypermobility

Abstract: Adolescent competitive swimmers with GJHS displayed no shoulder sensorimotor control deficiencies and no generally altered shoulder muscle activity pattern, except for decreased pectoralis major activity in BL-EO. Longitudinal studies are needed to investigate whether decreased pectoralis major activation contributes to the development of shoulder pain in swimmers with GJHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Therefore, in addition, there is a need for more functional testing. These tests may be divided into laboratory measures such as 3-D kinematic analysis [9] or stabilometric tests [23,24] and field measures. In view of the applicability in the clinical setting, although stabilometric tests may be useful in detecting proprioceptive and neuromuscular disorders, here we discuss only the field measurement tools.…”
Section: Which Tests Should We Use In Our Preventive Screening?mentioning
confidence: 99%
“…Therefore, in addition, there is a need for more functional testing. These tests may be divided into laboratory measures such as 3-D kinematic analysis [9] or stabilometric tests [23,24] and field measures. In view of the applicability in the clinical setting, although stabilometric tests may be useful in detecting proprioceptive and neuromuscular disorders, here we discuss only the field measurement tools.…”
Section: Which Tests Should We Use In Our Preventive Screening?mentioning
confidence: 99%
“…In competitive swimming, the incidence of shoulder pain is reported to be between 38%‐91% 1,5,6 . Potential risk factors for the high incidence of shoulder pain have included including, extrinsic (competitive level, swimming experience, training distance/volume/intensity, and swimming training equipment) and intrinsic factors (glenohumeral instability, abnormal range of motion, strength imbalance of rotator cuff muscles, and scapular dyskinesis) 7 …”
Section: Introductionmentioning
confidence: 99%
“…Findings regarding gender differences were inconsistent. Whereas most studies found GJH was more prevalent in girls [ 16 , 30 , 54 , 56 , 61 , 103 , 119 ], in others it was just a trend [ 41 , 52 , 99 , 105 , 117 ]. One study found a higher prevalence in boys [ 118 ] and one study found a higher prevalence in boys aged 6–10, while prevalence was higher in girls aged 11–15 and overall [ 108 ], and two studies found no gender differences [ 25 , 94 ].…”
Section: Resultsmentioning
confidence: 99%